Optimalisasi Line Balancing pada Proses Produksi PCB Line KMM-X704KN PT. XYZ - Rahmat Hidayat; Tri Ngudi Wiyatno; Dwi Indra Prasetya (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze and balance the production line in the assembly process using two Line Balancing methods, namely Helgeson–Birnie (H-B) and the Largest Candidate Rule (LCR), with a cycle time (CT) set at 2.28 minutes (137 seconds) based on the manual bottleneck workstation. The total element work time was recorded at 19.39 minutes, with a minimum required number of 9 workstations. The calculation results from both methods showed consistent and identical solutions, yielding 10 actual workstations (N_actual = 10). The line performance achieved a Line Efficiency (LE) of 85.04% with a Balance Delay (BD) of 14.96%. Although this efficiency is considered good, idle time analysis revealed a total waste of 3.41 minutes, most of which occurred at Workstation 10, which operated for only 0.20 minutes. These findings indicate that improvements should focus on restructuring the final workstation to eliminate waste, increase LE, and streamline total element time to approach the Takt Time, thereby optimizing overall line performance. This study provides practical recommendations for production management to enhance productivity and the efficiency of the assembly line.